O trabalho e o processo de saúde-doença das costureiras por facção região metropolitana de Goiânia/2010 - Pimentel, Lílian Cristina Teixeira (2011)
This research sought to identify the implications of environmental, social and work in the process of health - disease of women seamstresses by faction of the Metropolitan Area of Goiânia. Had as reference the Doctoral Thesis, Mujeres del trabajo that live at home - El tiempo de las trabajadores own de la ropa de Goiás dress, the type of study and research subjects 10 years later, it is referenced in this study as research-reference (Jonas / 2001). This is a qualitative study conducted with 34 seamstresses by faction in their own home which was located among the 59 selected intentionally seamstresses who participated in discussion groups of research-reference (Jonas/2001). Data were collected through interviews and the results obtained allowed to identify most of these women are older than 55 years, white, married, partisan, included in this work is by vocation, need to help out financially at home or lack of better job opportunities. Mostly have low education, excessive working hours, work more than 12 hours per week, shift work beyond 8 hours without receiving extra compensation and receive one to two minimum wages. Besides the professional work they perform domestic chores in their homes, which characterizes the double workday. The work environment is usually devoid of visual comfort, thermal, acoustic, securities with inadequate and mingles with the familiar environment. They are exposed to several risk factors physical, economic and environmental manifested in health problems identified at all partisan. They are more common: the musculoskeletal disorders, spine problems, digestive disorders, hypertension and varices. Most seamstresses identified as a disadvantage in that said free work, lack of rights and social guarantees, and the advantage of the fact that he reconciled the various roles of mother, wife and homemaker. Regarding the expected achievements expressed that most of them, was to contribute to education and training of children. Passed 10 years after the 1st investigation that served as reference for this work, the seamstresses attribute the health problems faced by them as hereditary factors, without a conscious attitude on the conditioning to which they are referred by the type of work.Therefore, it can be stated that, in general, they still are not aware of the current issues that occur in the workplace and is permeated by violations of the diversity of risk factors present in the work of faction at home, and impact of work overload accumulated work at home with the day's housework and care of the family, responsible for diseases and painful manifestations.